A Country for My Daughter - Blankenberg, Lucilla (South Africa, 2010)
"A Country For My Daughter" Nonkosi travels around the country investigating the stories of brave women whose court
cases have transformed the law in South Africa for the better. The cases range from rape within a family to holding the
Minister of Safety and Security liable, in cases where police were involved in violence against women. Through these stories,
Nonkosi learns of the laws available to protect South African women and how they can be used.
Verzio Film Festival Submission
Keywords: Documentary films